National Stakeholder Consultation on Nutrition-Sensitive Agri-Food Systems Policy and Literature Review in Cambodia - Duong Thi Thanh; Huynh Thi Thanh Tuyen (Alliance of Bioversity International and CIAT and ILRI, 2022)
The report is about the national stakeholder consultation on nutrition-sensitive agrifood systems policy event co-organized by the International Institute of Rural Reconstruction (IIRR), the Alliance of Bioversity and CIAT (the Alliance), the Council for Agricultural and Rural Development (CARD), and the Scaling Up Nutrition Civil Society Alliance (SUN CSA) in Cambodia on 13 December 2022.